Anterior makeover on fractured teeth by simple composite resin restoration - Eric Priyo Prasetyo (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: In daily practice dentists usually treat tooth fractures with more invasive treatments such as crown, veneer and bridges which preparation require more tooth structure removal. While currently there is trend toward minimal invasive dentistry which conserves more tooth structure. This is enhanced with the vast supply of dental materials and equipment in the market, including restorative materials. Provided with these supporting materials and equipment and greater patient’s demand for esthetic treatment, dentists must aware of the esthetics and basic principle of conserving tooth which should retain tooth longevity. Purpose: This article showed that a simple and less invasive composite resin restoration can successfully restore anterior esthetic and function of fractured teeth which generally treated with more invasive treatment options. Case: A 19 year-old female patient came with fracture on 21 and 22. This patient had a previous history of dental trauma about nine years before and was brought to a local dentist for debridement and was given analgesic, the involved teeth were not given any restorative treatment. Case management: The fractured 21 and 22 were conventionally restored with simple composite resin restoration. Conclusion: Fracture anterior teeth would certainly disturbs patient’s appearance, but these teeth could be managed conservatively and economically by simple composite resin restoration.Latar belakang: Dalam praktek sehari-hari pada umumnya dokter gigi merawat fraktur dengan restorasi invasif seperti mahkota, veneer dan jembatan yang semuanya memerlukan pengambilan jaringan gigi lebih banyak, sedangkan saat ini trend perawatan gigi lebih menuju kearah invasif minimal yang mempertahankan jaringan gigi sebanyak mungkin. Keadaan ini ditunjang oleh tersedianya berbagai macam bahan dan peralatan kedokteran gigi di pasaran, termasuk bahan restorasi. Dengan tersedianya bahan dan peralatan yang mendukung serta tingginya permintaan pasien akan perawatan estetik, dokter gigi harus mengetahui estetik dan prinsip dasar dari konservasi gigi yaitu mempertahankan gigi selama mungkin. Tujuan: Laporan kasus ini menunjukkan bahwa restorasi resin komposit sederhana yang tidak invasif dapat memperbaiki estetik dan fungsi geligi fraktur yang umumya dirawat dengan macam restorasi yang lebih invasif. Kasus: Seorang wanita berusia 19 tahun datang dengan fraktur pada gigi 21 dan 22. Pasien tersebut memiliki riwayat trauma pada giginya sejak sembilan tahun sebelumnya dan telah dibawa ke dokter gigi untuk debridemen dan pemberian analgesik saja, tanpa perawatan restoratif. Tatalaksana kasus: Gigi fraktur pada 21 dan 22 diperbaiki dengan restorasi resin komposit sederhana. Kesimpulan: Fraktur pada gigi anterior akan sangat mengganggu penampilan pasien, akan tetapi fraktur tersebut dapat dirawat secara konservatif dan ekonomis dengan restorasi resin komposit sederhana.